Peningkatan Kompetensi Guru Melalui Peran Kepala Madrasah Sebagai Motivator di MTs Al Ihsaniya Sarang Burung, Jambi Luar Kota, Muara Jambi - Sunardi; Abu Darim (Suria Academic Press, 2025)
This study aims to explore the role of the Headmaster as a motivator in improving teacher competence at Madrasah Tsanawiyah Al Ikhsaniya Sarang Burung, Jambi Luar Kota, Muaro Jambi. The research focuses on three aspects: planning, implementation, and outcomes of improving teacher competence through the Headmaster's role as a motivator. The research method used is descriptive qualitative, with a case study approach involving in-depth interviews with the Headmaster, teachers, and direct observation of the activities related to teacher competence development at the Madrasah. The results of the study show that: first, in the planning phase, the Headmaster designs professional development programs that address the teachers' needs, taking into account internal evaluations and the dynamics of the field. Second, during implementation, the Headmaster actively acts as a motivator by providing encouragement, direction, and recognition of teachers' achievements. The Headmaster also facilitates collaborative activities and team-based development. Third, the outcomes of the competence improvement are reflected in positive changes in teaching performance, curriculum understanding, and the use of technology in the learning process. The conclusion of this study indicates that the Headmaster’s role as a motivator significantly influences the planning, implementation, and outcomes of teacher competence improvement. An active and inspiring Headmaster can create an environment that supports teachers' professional development, ultimately leading to improved educational quality.